2019
DOI: 10.1371/journal.pone.0212576
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and oviposition deterrence of essential oils of Clinopodium nubigenum and Lavandula angustifolia against the myiasis-inducing blowfly Lucilia sericata

Abstract: Cutaneous myiasis is a severe worldwide medical and veterinary issue. In this trial the essential oil (EO) of the Andean medicinal plant species Clinopodium nubigenum (Kunth) Kuntze was evaluated for its bioactivity against the myiasis-inducing blowfly Lucilia sericata (Meigen) (Diptera Calliphoridae) and compared with that of the well-known medicinal plant species Lavandula angustifolia Mill. The EOs were analysed and tested in laboratory fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 66 publications
1
24
0
1
Order By: Relevance
“…In particular, among the foodborne disease bacteria, we observed a strong activity against E. coli, while S. enterica was the most resistant strain. In line with these results, S. enterica was found to be the most resistant microbial strain for the EOs extracted from C. nubigenum and L. angustifolia [28]. Such antimicrobial activity of the EOs is important since Calliphoridae are vectors of numerous microorganisms and foodborne pathogens [1][2][3].…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…In particular, among the foodborne disease bacteria, we observed a strong activity against E. coli, while S. enterica was the most resistant strain. In line with these results, S. enterica was found to be the most resistant microbial strain for the EOs extracted from C. nubigenum and L. angustifolia [28]. Such antimicrobial activity of the EOs is important since Calliphoridae are vectors of numerous microorganisms and foodborne pathogens [1][2][3].…”
Section: Discussionmentioning
confidence: 71%
“…The responsiveness of C. vomitoria to the three EOs was confirmed by the results of the oviposition deterrence bioassay that showed that A. sativum, R. officinalis, and S. officinalis EOs are able to exert a clear deterrent activity against C. vomitoria females' oviposition. Such results are in good agreement with previous experiments showing a strong oviposition deterrence by Artemisia dracunculus L. and A. annua L. (Asteraceae) EOs [19] against C. vomitoria and of Lavandula angustifolia Mill., and Clinopodium nubigenum (Kunth) EOs against Lucilia sericata Meigen (Diptera Calliphoridae) [28]. A repellent effect of EOs was also observed by Callander and James [38] who obtained the complete inhibition of oviposition of L. cuprina on wool treated with tea tree (Melaleuca alternifolia Maiden & Betche) EO.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Pest control could be achieved through the integration of multiple tactics; among the possible alternatives to synthetic pesticides, the use of chemical stimuli to manipulate insect behavior is considered a suitable biotechnical control tool in the management of several insect pests 29 . Some insecticides, beside lethal toxicity, affect insect behavior preventing settling on the host plant, probing and feeding, oviposition, and virus transmission 33,34 . Therefore, behavioral effects caused by an insecticide that is apparently non-toxic for the insect in conventional tests, could in fact permit to contain the insect populations and associated yield losses.…”
Section: Discussionmentioning
confidence: 99%
“…antimicrobiano (Bedini et al, 2019), pediculicida (Limoncu et al, 2017), repelente de insectos (Štefanidesová et al, 2017). A: Condimento para salsas, ensaladas, estofados y dulces, saborizante de bebidas.…”
Section: Discusión Y Conclusionesunclassified